2019
DOI: 10.18203/2320-6012.ijrms20193373
|View full text |Cite
|
Sign up to set email alerts
|

Vascular malformations: a hospital based study

Abstract: Background: Vascular anomalies comprise a widely heterogeneous group of lesions. Diagnosis and management of these lesions present challenges to the surgeons, radiologists and histopathologists. Accurate classification of these lesions results in appropriate therapy. Aim of the study is to study the role of histopathology and histochemical stain in the diagnosis of vascular malformationMethods: The present study is a hospital based observational study on vascular malformations over a period of three years from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…One study showed 65.71% agreement between clinical diagnosis and histopathology in vascular malformations. 21 They concluded that the histopathologic examination helped in subcategorizing various vascular malformations, and thus, combining diagnostic features will reduce diagnostic difficulties and help in proper patient management. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed 65.71% agreement between clinical diagnosis and histopathology in vascular malformations. 21 They concluded that the histopathologic examination helped in subcategorizing various vascular malformations, and thus, combining diagnostic features will reduce diagnostic difficulties and help in proper patient management. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study also confirmed a major problem of misuse of the nomenclature as has been recognized previously. 3 , 21 , 36 Several cases that were not recognized as malformations were initially diagnosed as angioma, which can lead to improper treatment. Sampling bias may occur in case of small biopsies, and thus, it is not recommended to apply as a single diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%